Effects of outer mouth mutations on hERG channel function: a comparison with similar mutations in the Shaker channel. - Fan, J S (1999)
The fast-inactivation process in the hERG channel can be affected by mutations in the pore or S6 domain, similar to the C-type inactivation in the Shaker channel. However, differences in the kinetics and voltage dependence of inactivation between these two channels suggest that different structural determinants may be involved. To explore this possibility, we mutated a serine in the outer mouth region of hERG (S631) to residues of different physicochemical properties and compared the resulting changes in the channel's inactivation process with those resulting from mutations of an equivalent position in the Shaker channel (T449). The most dramatic differences are seen when this position is occupied by a charged residue: S631K and S631E disrupted C-type inactivation in hERG, whereas T449K and T449E facilitate C-type inactivation in Shaker. S631K and S631E also disrupted the K selectivity of hERG pore, a change not seen in T449K or T449E of Shaker. To further study why there are such differences, we replaced S631 with cysteine. This allowed us to manipulate the properties of thiol groups at position 631 and correlate side-chain properties here with changes in channel function. S631C behaved like the wild-type channel when the thiol groups were in the reduced state. Oxidizing thiol groups with H2O2 or modifying them with MTSET or MTSES disrupted C-type inactivation and K selectivity, similar to the phenotype of S631K and S631E. The same thiol-modifying maneuvers did not affect the wild-type channel function. Our results suggest differences in the outer mouth structure between hERG and Shaker, and we propose a "molecular spring" hypothesis to explain these differences.